2011
DOI: 10.1016/j.ijpara.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transfection of developmentally competent Brugia malayi infective larvae

Abstract: Transient transfection of isolated Brugia malayi embryos by biolistics has proven to be useful in defining promoter structure and function in this parasite. However, isolated transfected embryos are developmentally incompetent. A method of producing developmentally competent transfected parasites is therefore needed. We report that L3 parasites can be chemically transfected in situ in the peritoneal cavity of a gerbil with a construct consisting of a secreted luciferase reporter gene containing a promoter, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…This method has been used widely for integrative transformation in C. elegans (Praitis, 2006; Schweinsberg and Grant, 2013), and for transient transformation of filariae (Higazi and Unnasch, 2013) and ascarid roundworms (Davis et al 1999). However, while this method has proven effective for transient expression of nucleic acid constructs, the level of mortality among bombarded parasitic nematodes has prevented its use thus far in derivation of viable, developing parasites that stably express transgenes (Xu et al 2011). Also, the low frequency of transgene integration into the chromosomes of C. elegans following biolistic transfer can be offset by a selection process in which worms with a mutation in unc-119 that impairs motility and dauer formation are rescued by a plasmid encoding wild-type unc-119 co-transferred with the construct of interest (Schweinsberg and Grant, 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…This method has been used widely for integrative transformation in C. elegans (Praitis, 2006; Schweinsberg and Grant, 2013), and for transient transformation of filariae (Higazi and Unnasch, 2013) and ascarid roundworms (Davis et al 1999). However, while this method has proven effective for transient expression of nucleic acid constructs, the level of mortality among bombarded parasitic nematodes has prevented its use thus far in derivation of viable, developing parasites that stably express transgenes (Xu et al 2011). Also, the low frequency of transgene integration into the chromosomes of C. elegans following biolistic transfer can be offset by a selection process in which worms with a mutation in unc-119 that impairs motility and dauer formation are rescued by a plasmid encoding wild-type unc-119 co-transferred with the construct of interest (Schweinsberg and Grant, 2013).…”
Section: Future Directionsmentioning
confidence: 99%
“…(Junio et al 2008) may allow knock-out or knock-in of specific pathway genes to identify the limiting steps. Recently, Xu et al (2011) reported chemical transfection of infective L3 larvae of B. malayi in situ, with subsequent stable expression of a luciferase reporter gene. Generation of transgenic parasites therefore has the potential to enhance RNAi silencing mechanisms and also provide a means of expressing dsRNA from hairpin constructs which may overcome the limitations of environmental RNAi.…”
Section: F U T U R E P E R S P E C T I V E Smentioning
confidence: 99%
“…Mongolian gerbils (Meriones unguiculatus) are used in biomedical research, such as in studies of infections with Helicobacter pylori (Wu et al, 2008) and Brugia malayi (Xu et al, 2011). Because of the absence of mAbs specific to gerbil Igs, antibodies in gerbil sera have been measured by agglutinin assay (Kai et al, 2002) and polyclonal antibodies (pAbs) to mouse immunoglobulin (Ig) isotypes showing cross-reactivity to their gerbil counterparts (Amorim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%